Peran Kelembagaan Petani Sawit Swadaya Dalam Program Peremajaan Sawit Rakyat (PSR) Di Kabupaten Indragiri Hilir - Agung Pramono; Tri Kurniaty; Zulfikar; Riyadi Mustofa (SINTA Journal (Science, Technology, and Agricultural), 2025)
The Smallholder Palm Oil Rejuvenation Program (PSR) is a strategic government policy aimed at improving the productivity and sustainability of smallholder oil palm plantations, in which farmer institutions play a pivotal role in ensuring effective implementation. This study aims to analyze the factors influencing the role of independent smallholder farmer institutions in supporting the implementation of the PSR program in Indragiri Hilir Regency, Riau Province. A quantitative approach was applied through a survey of 200 independent oil palm farmers, and data were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with SmartPLS software. The results show that Institutional Managerial (β = 0.337; p < 0.001), Institutional Performance (β = 0.329; p < 0.001), and Technical and Productivity (β = 0.317; p < 0.001) have a positive and significant effect on the Institutional Role of smallholder farmers. The model demonstrates strong predictive capability, with an R² value of 0.748, indicating that these factors collectively explain a substantial proportion of the variance in institutional effectiveness. These findings highlight the importance of strengthening internal institutional capacity through sound governance, enhanced performance accountability, and improved technical competence to optimize the role of farmer institutions in supporting the success of the PSR program. The study recommends managerial training, institutional transparency, and technology transfer as key strategies to reinforce the strategic role of farmer institutions in achieving sustainable palm oil smallholder development.